Bacterial strains decrease solubility of potassium in the soil (Bioscience Journal, 2020)
Current study verifies whether inoculation with strains of diazotrophic bacteria, with proven ability to solubilize potassium (K) in vitro, contributes towards the release of K in the soil after fertilization with phonolite rock powder. The experiment was conducted in containers with 0.3 dm-3 of soil containing low potassium content. Fifteen treatments were used, namely, 12 inoculated with the bacterial strains, a control treatment (without phonolite and without inoculation), one containing phonolite without inoculation and one containing KCl, soluble fertilizer, without inoculation. In treatments with phonolite and KCl, the doses of these materials were applied to provide the soil with 195 mg dm-3 of K. A completely randomized design with four replications was used. The soil was incubated during 90 days at room temperature and humidity at about 70% retention capacity. After this period, the content of K+ (Mehlich and resin), pH value and potential acidity (H+Al) were evaluated. Phonolite, associated with inoculation with most bacterial strains, increased the availability of potassium in the soil, pH rate and reduced potential acidity. Among the strains tested, UNIFENAS 100-01, UNIFENAS 100-16, UNIFENAS 100-27, UNIFENAS 100-39 and UNIFENAS 100-93 were the most efficient for the solubilization of K+ of the phonolite. In spite of the observed results, K content released by the bacterial strains in the soil decreased when compared to in vitro conditions, thus justifying the need for studies on bio-solubilization of soil to select the most efficient strains in the process.